Dynamic reconfiguration to optimize energy production on moving photovoltaic panels. - Merino-Córdoba, Salvador; Martínez-del-Castillo, Javier; Guzmán-Navarro, Francisco; Lara-Fernández, Juan de Dios; Guzmán-Sepúlveda, Rafael; Sánchez-Pacheco, Francisco José; Heredia-Larrubia, Juan Ramón; Sidrach-de-Cardona-Ortin, Mariano (MDPI, 2023)
Urban transport systems play a major role in the development of today’s societies, but they require technological changes to reduce their environmental impact. The problem lies in their level of autonomy, which is why electrical energy production systems are proposed for self-consumption, efficiently feeding their accumulators. As the energy provided by photovoltaic installations has lower recharge speeds, conventional systems with high transfer amperage and higher voltage are required. For this reason, solar installations are used for additional services and to support their autonomy. The present work tries to find the best solution for both constant voltage and peak current systems. Once found, these solutions will be applied in real time for the dynamic recharging of battery packs, trying to achieve vehicles that are progressively more energetically autonomous. To solve these situations, a new computational method for calculating voltage and amperage has been developed in this work, based on Dijkstra’s minimum path search algorithm on graph theory, adapted to electrical circuits. Once this algorithm has been established, the panel performance analysis sensors, developed at the University of Malaga, are combined with different electronic solutions described in this article (Wi-Fi relay devices using esp8266 chips or feeding these relays through panels and establishing the voltage drop to switch the connection), achieving precise and sufficiently fast solutions at very low cost. Both series and parallel transitions are possible, depending on the type of energy generation required. The theoretical solutions using Minkowski paths, analyzed in the past, have been simulated and subsequently constructed in this paper, indicating the diagrams necessary for their realization.
Keywords: Células fotovoltaicas; Energía fotovoltaica - Generación; Dijkastra; Photovoltaic panels; Energy efficiency; Graph theory; Transport means